Structure–activity relationship study of 4-substituted piperidines at Leu26 moiety of novel p53–hDM2 inhibitors. Issue 11 (1st June 2016) - Tian, Yuan; Ma, Yao; Gibeau, Craig R.; Lahue, Brian R.; Shipps, Gerald W.; Strickland, Corey; Bogen, Stéphane L.
Graphical abstract: Abstract: Led by the structural information of the screening hit with mDM2 protein, a structure modification of Leu26 moiety of the novel p53–hDM2 inhibitors was conducted. A structure–activity relationship study of 4-substituted piperidines revealed compound20t with good potencies and excellent CYP450 profiles.